PEG Graft Polymer Carriers of Antioxidants: In Vitro Evaluation for Transdermal Delivery - Justyna Odrobińska; Magdalena Skonieczna; Dorota Neugebauer (MDPI AG, 2020)
The in vitro biochemical evaluation of the applicability of polymers carrying active substances (micelles and conjugates) was carried out. Previously designed amphiphilic graft copolymers with retinol or 4-n-butylresorcinol functionalized polymethacrylate backbone and poly(ethylene glycol) (PEG) side chains that included Janus-type heterografted copolymers containing both PEG and poly(ε-caprolactone) (PCL) side chains were applied as micellar carriers. The polymer self-assemblies were convenient to encapsulate arbutin (ARB) as the selected active substances. Moreover, the conjugates of PEG graft copolymers with ferulic acid (FA) or lipoic acid (LA) were also investigated. The permeability of released active substances through a membrane mimicking skin was evaluated by conducting transdermal tests in Franz diffusion cells. The biological response to new carriers with active substances was tested across cell lines, including normal human dermal fibroblasts (NHDF), human epidermal keratinocyte (HaCaT), as well as cancer melanoma (Me45) and metastatic human melanoma (451-Lu), for comparison. These polymer systems were safe and non-cytotoxic at the tested concentrations for healthy skin cell lines according to the MTT test. Cytometric evaluation of cell cycles as well as cell death defined by Annexin-V apoptosis assays and senescence tests showed no significant changes under action of the delivery systems, as compared to the control cells. In vitro tests confirmed the biochemical potential of these antioxidant carriers as beneficial components in cosmetic products, especially applied in the form of masks and eye pads.